Mãos de quem planta, colhe e entrega: uma avaliação do Programa Nacional de Alimentação Escolar (PNAE) no município de Barbalha-CE - Brito, Maria Alane Pereira de (2024)
This research evaluated the National School Feeding Program (Pnae) regarding the impact of purchasing products from family farming on the lives of recipients farmers in the municipality of BarbalhaCE, from 2019 to 2022. To this end, the objectives were specific: Identify who are the family farmers who participate in the PNAE, through their perceptions and collection of socioeconomic data; Investigate how the Program impacts the lives of recipients, with regard to income and its possible consequences; Examine the relationship between farmers and the Pnae public policy and the promotion of food and nutritional security; and Investigate the role of farmers in the environmental development of the municipality. Furthermore, it used the SustainabilityBased Assessment (ABS) as an evaluative approach, proposing an analysis based on the four dimensions of sustainability: social, economic, institutionalpolitical and environmental. Qualitative Research and Case Study were adopted as a methodological strategy, with data collection procedures being Bibliographical, Documentary and Field Research, where Semi- structured Interviews, Forms and InDepth Interviews were carried out with recipient farmers(as) and representatives of public authorities active in the public policy in question. Furthermore, Discourse Analysis was the method chosen to analyze the data collected between April and August 2023. It was therefore evident that the integration of local products into school meals not only strengthens food security in schools, but also emerges as a transformative vector in rural communities. The challenges faced by these actors and actresses were also observed, such as the need to improve policies to encourage family farming, and the increase in incentives for production, through technical assistance, and the guarantee of fair prices for the products supplied, as well as such as, the significant changes and impacts on their lives resulting from their work at Pnae.